Evaluation of the relationship between attention deficit hyperactivity disorder symptoms and chronotype - Tarakçıoğlu, Mahmut Cem; Kadak, Muhammed Tayyib; Akkın Gürbüz, Gözde; Poyraz, Burç Çağrı; Erdo?an, Fırat; Aksoy, Umut Mert (AVES, 2018)
Introduction: The aim of the study is to investigate the relationship between circadian characteristics and behavioral problems in children with Attention Deficit Hyperactivity Disorder (ADHD) (n=53), and to compare this group with healthy controls (n=38). Method: Fifty-three medication-free children with ADHD, aged 6-12 years. and 38 healthy children, age and sex matched, participated. Parents completed the Conners' Parent Rating Scale-Revised, the Children's Chronotype Questionnaire (CCTQ), and the Children's Sleep Habits Questionnaire (CSHQ) to assess sleep variables. Results: ADHD children had more sleep-onset problems and parasomnias (in CSHQ) compared to healthy controls. However; circadian preferences did not differ between the groups in CCTQ scores. Another important finding was a mild correlation between parasomnia, bedtime on schooldays, and ADHD symptoms. Conclusion: Our study showed that children with ADHD showed more resistance to going to bed than did controls on school days. However, in contrast to our hypothesis, morningness/eveningness preference did not differ from controls in ADHD children.

Amaç: Bu çalışmada, Dikkat Eksikliği Hiperaktivite Bozukluğu (DEHB) tanılı çocuklar (n=53) ve sağlıklı kontrollerde (n=38) sirkadyen özellikler ve davranışsal sorunlar arasındaki ilişkinin incelenmesi ve karşılaştırılması amaçlanmıştır. Yöntem: DEHB tanısı alan, daha önce tedavi almamış, 6–12 yaş arası 53 çocuk ile yaş ve cinsiyet açısından benzer özellikte olan 38 sağlıklı çocuk çalışmaya alınmıştır. Uyku ile ilgili değişkenlerin incelenmesi için ebeveynler Conners Anababa Dereceleme Ölçeği Yenilenmiş Uzun Formu, Çocuk Kronotip Ölçeği (CKÖ) ve Çocuk Uyku Alışkanlıkları Ölçeklerini (ÇUAÖ) doldurmuştur. Bulgular: DEHB tanılı çocuklarında sağlıklı kontrollere göre daha fazla uykuya dalma ve parasomni şikayetleri vardır. Ancak, CKÖ’ye göre sirkadyen tercihleri açısından her iki grup arasında anlamlı fark bulunmamıştır. Parasomni ve okul günleri yatakta uyku için geçirilen zaman ile DEHB belirtileri arasında orta derecede korelasyon bulunmuştur. Sonuç: Çalışmamızda DEHB tanılı çocuklarda okul günlerinde daha fazla uykuya direnç görülmektedir. Ancak, çalışmanın hipotezinin aksine, Sabahlılık/akşamlılık yönelimi açısından DEHB ile sağlıklı kontroller arasında anlamlı farklılık bulunamamıştır.
Dikkat eksikliği hiperaktivite bozukluğu belirtileri ile kronotip arasındaki ilişkinin incelenmesi
WOS: 000450095400010
PubMed ID: 30042642
Keywords: ADHD; Sleep-Wake Cycle; Sleep Habits; Circadian Preference; DEHB; Uyku Alışkanlıkları; Uyku-Uyanıklık Döngüsü; Sirkadyen Yönelim